Fluorescent photoinduced electron transfer sensing of anions using charge neutral chemosensors - Glynn, Mark (Trinity College (Dublin, Ireland). School of Chemistry, 2003)
The primary aim of this research was to design, synthesise and analyse anion sensors using fluorescence detectors. The thesis is spread over five chapters. Chapter one, the introduction begins with a brief back round to the area of supra molecular chemistry followed by an in depth analysis of the current research in the field of anion binding. Initially the examples, illustrations are of different host/guest systems developed, positively charged. Both metal free hosts and metal based hosts. This chapter also outlined the brief history of anion binding using fluorescence detector up to and including the most recent advances in this area. Chapter two deals with the thiourea and area based PET sensors designed with one binding site. This chapter outlines the various synthetic routes investigated in attempt to synthesis these hosts. The second and third chapter outlines the synthetic routes investigated in the attempts to synthesis mono and big based receptors respectfully. This synthesis is followed by an in depth discussion on the analytical techniques used to determine the sensing ability of these read molecules. Chapter two specifically deals with sensors containing one bind site and measures the affinity and selectivity of these of these sensors towards biologically significant mono valent anions. Chapter three discusses the synthesis and analysis of sensors containing two binding sites. The affinity of these sensors towards both monovalent and divalent anions are discussed with this chapter. The conclusions obtained from the fluorescence spectroscopy are then substantiated using NMR measurements. Chapter four discusses the work conducted in conjunction with Professor Davis on cholic acid derivatives. The synthetic routes investigated in effort to synthesis fluorescent derivatives of cholic acid based anion binders is discussed here in detail. Chapter five contains the experimental detail.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin